A Janus Au–Polymersome Heterostructure with Near‐Field Enhancement Effect for Implant‐Associated Infection Phototherapy. Issue 3 (11th December 2022) - Chen, Chuanshuang; Chu, Guangyu; He, Wanting; Liu, Yannan; Dai, Kai; Valdez, Jesus; Moores, Audrey; Huang, Pei; Wang, Zhaohong; Jin, Jiale; Guan, Ming; Jiang, Wenfeng; et al.
Abstract: Polymer–inorganic hybrid Janus nanoparticles (PI‐JNPs) have attracted extensive attention due to their special structures and functions. However, achieving the synergistic enhancement of photochemical activity between polymer and inorganic moieties in PI‐JNPs remains challenging. Herein, the construction of a novel Janus Au–porphyrin polymersome (J‐AuPPS) heterostructure by a facile one‐step photocatalytic synthesis is reported. The near‐field enhancement (NFE) effect between porphyrin polymersome (PPS) and Au nanoparticles in J‐AuPPS is achieved to enhance its near‐infrared (NIR) light absorption and electric/thermal field intensity at their interface, which improves the energy transfer and energetic charge‐carrier generation. Therefore, J‐AuPPS shows a higher NIR‐activated photothermal conversion efficiency (48.4%) and generates more singlet oxygen compared with non‐Janus core–particle Au–PPS nanostructure (28.4%). As a result, J‐AuPPS exhibits excellent dual‐mode (photothermal/photodynamic) antibacterial and anti‐biofilm performance, thereby significantly enhancing the in vivo therapeutic effect in an implant‐associated‐infection rat model. This work is believed to motivate the rational design of advanced hybrid JNPs with desirable NFE effect and further extend their biological applications. Abstract : A novel Janus Au–porphyrin polymersome heterostructure (J‐AuPPS) is constructed by a facile one‐step photocatalytic synthesis process. The near‐field enhancement effect between the porphyrin polymersome and Au nanoparticles in the as‐prepared J‐AuPPS is achieved to synergistically improve the photochemical activity. As a result, J‐AuPPS shows enhanced in vitro and in vivo phototherapy effects in bacterial ablation and combating implant‐associated infections.